Transcriptional Analysis of Sepsis-Induced Activation and Damage of the Adrenal Endothelial Microvascular Cells - Chen, Lan-Sun; Singh, Sumeet P.; Müller, Gregor; Bornstein, Stefan R.; Kanczkowski, Waldemar (Frontiers in Endocrinology, 2020)
Bacterial sepsis is a serious threat to the body homeostasis and is often associated with high mortality in non-coronary intensive stations. In order to survive sepsis, rapid activation of the hypothalamus-pituitary-adrenal gland axis and sympathomedullary system is necessary. In many patients with sepsis, the function of those two arms of the stress system is dysregulated with underlying mechanisms remaining unknown. In our previous experimental studies, we have demonstrated that LPS-induced systemic inflammation and CLP-induced peritonitis can result in adrenal gland damage. Histological and transcriptomic analysis revealed a potential involvement of the adrenal microvascular endothelium in this process. However, our knowledge about the function of adrenal microvascular cells during sepsis is scarce. In the present study, we have characterized transcriptomic alterations in isolated mouse adrenal microvascular endothelial cells induced by systemic administration of bacterial LPS. Our results revealed that LPS induced a distinct transcriptomic profile in the adrenal microvascular cells, including multiple genes regulating inflammation, activation of the coagulation cascade and vascular permeability. Activation of those genes may be potentially involved in the damage to the microvascular endothelium and altogether contribute to the sepsis-mediated adrenal dysregulation.